Chronic Sleep Deprivation Blocks Voluntary Morphine Consumption but Not Conditioned Place Preference in Mice - Eacret, Darrell; Lemchi, Crystal; Caulfield, Jasmine I.; Cavigelli, Sonia A.; Veasey, Sigrid C.; Blendy, Julie A. (Frontiers in Neuroscience, 2022)
The opioid epidemic remains a significant healthcare problem and is attributable to over 100,000 deaths per year. Poor sleep increases sensitivity to pain, impulsivity, inattention, and negative affect, all of which might perpetuate drug use. Opioid users have disrupted sleep during drug use and withdrawal and report poor sleep as a reason for relapse. However, preclinical studies investigating the relationship between sleep loss and substance use and the associated underlying neurobiological mechanisms of potential interactions are lacking. One of the most common forms of sleep loss in modern society is chronic short sleep (CSS) (<7 h/nightly for adults). Here, we used an established model of CSS to investigate the influence of disrupted sleep on opioid reward in male mice. The CSS paradigm did not increase corticosterone levels or depressive-like behavior after a single sleep deprivation session but did increase expression of Iba1, which typically reflects microglial activation, in the hypothalamus after 4 weeks of CSS. Rested control mice developed a morphine preference in a 2-bottle choice test, while mice exposed to CSS did not develop a morphine preference. Both groups demonstrated morphine conditioned place preference (mCPP), but there were no differences in conditioned preference between rested and CSS mice. Taken together, our results show that recovery sleep after chronic sleep disruption lessens voluntary opioid intake, without impacting conditioned reward associated with morphine.